2019
DOI: 10.1037/emo0000426
|View full text |Cite
|
Sign up to set email alerts
|

Smiling through the shyness: The adaptive function of positive affect in shy children.

Abstract: Most research treats shyness as a homogenous phenomenon when examining its correlates and consequences, which limits the identification of specific groups of shy children who may be at differential risk for maladaptive social outcomes. Here, we examined whether different types of shyness were uniquely associated with social adjustment and physiological stress reactivity in school-age children (n = 92; Mage = 7.47 years; SD = 2.23 years). During the completion of a videotaped self-presentation task, behavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 73 publications
(142 reference statements)
4
38
2
Order By: Relevance
“…The experimenter placed a video camera in front of the child and asked them to give a short speech about their most recent birthday. Self-presentation tasks such as this are widely used to elicit shy/anxious behaviors in children (Poole & Schmidt, 2018;Theall-Honey & Schmidt, 2006).…”
Section: Birthday Speech Self-presentation Taskmentioning
confidence: 99%
“…The experimenter placed a video camera in front of the child and asked them to give a short speech about their most recent birthday. Self-presentation tasks such as this are widely used to elicit shy/anxious behaviors in children (Poole & Schmidt, 2018;Theall-Honey & Schmidt, 2006).…”
Section: Birthday Speech Self-presentation Taskmentioning
confidence: 99%
“…First, the expression of positive affect may signal one's interest in social interaction (i.e., sociability) and serve an appeasement function to social partners which may help facilitate approach from others as well as fulfill the positive shy individual's social affiliative desires (Sroufe & Waters, 1976). Indeed, empirical support has found that positive shyness tends to be associated with approach-related motivations as indicated by higher levels of sociability from toddlerhood to middle childhood (Colonnesi et al, 2014(Colonnesi et al, , 2017Poole & Schmidt, 2019b). Second, according to the tensionreleasing hypothesis of positive affect, the expression of positivity plays a regulatory function in modulating arousal during stressful situations (Sroufe & Waters, 1976).…”
mentioning
confidence: 99%
“…That is, while positive shy children may experience fear in a social situation, they are simultaneously regulating their arousal through positive emotional expressions which allow them to remain oriented and engaged with their social partner (Colonnesi et al, 2014(Colonnesi et al, , 2017Nikoli c et al, 2016;Reddy, 2000;Sroufe & Waters, 1976). This social engagement during feared social situations can result in social competence and protect the shy child from developing behaviors associated with emotion dysregulation such as anxiety (Colonnesi et al, 2014(Colonnesi et al, , 2017Poole & Schmidt, 2019b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Person‐oriented approaches are regarded as useful in classifying individuals who share common characteristics and effectively categorize individuals who have conceptually and empirically different behavioral profiles (see Bergman & Trost, , for a review). Indeed, previous research studying shyness (LoBue & Pérez‐Edgar, ; Poole & Schmidt, ; Schmidt, ; Wolfe & Bell, ) and related constructs such as social withdrawal (Coplan et al, ; Nelson, ) and behavioral inhibition (Coplan, Wilson, Frohlick, & Zelenski, ; Kagan et al, ) have illustrated the utility of using a person‐oriented approach in studying social behavior. Likewise, children in the present study were classified as high shy and low shy using a median split (high shy: n = 19, M = 3.18; low shy: n = 18, M = 1.64; t (35) = −9.45, p < 0.001, d = 3.15).…”
Section: Methodsmentioning
confidence: 99%